Potential of Murine IgG1 and Human IgG4 to Inhibit the Classical Complement and Fcγ Receptor Activation Pathways - Lilienthal, Gina-Maria; Rahmöller, Johann; Petry, Janina; Bartsch, Yannic C.; Leliavski, Alexei; Ehlers, Marc (Frontiers in Immunology, 2018)
IgG antibodies mediate their effector functions through the interaction with Fcgamma receptors and the complement factors. The main IgG-mediated complement activation pathway is induced through the binding of complement C1q to IgG antibodies. This interaction is dependent on antigen-dependent hexamer formation of human IgG1 and IgG3 to increase the affinity for the six-headed C1q molecule. In contrast, human IgG4 fails to bind to C1q. Instead, it has been suggested that human IgG4 can block IgG1 and IgG3 hexamerization required for their binding to C1q and activating the complement. Here, we show that murine IgG1, which functionally resembles human IgG4 by not interacting with C1q, inhibits the binding of IgG2a, IgG2b and IgG3 to C1q in vitro and suppresses IgG2a-mediated complement activation in a haemolytic assay in an antigen-dependent and IgG subclass-specific manner. From this perspective, we discuss the potential of murine IgG1 and human IgG4 to block the complement activation as well as suppressive effects of sialylated IgG subclass antibodies on Fcgamma receptor-mediated immune cell activation. Accumulating evidence suggest that both mechanisms seem to be responsible for preventing uncontrolled IgG (auto)antibody-induced inflammation in mice and humans. Distinct IgG subclass distributions and functionally opposite IgG Fc glycosylation patterns might explain different outcomes of IgG-mediated immune responses and provide new therapeutic options through the induction, enrichment or application of antigen-specific sialylated human IgG4 to prevent complement and Fcgamma receptor activation as well.